Second chance with his princess - Winters, Rebecca, 1940- (Winters, Rebecca, 1940- Baldasseri royals, 2022)
"It's been ten long years since Luca Torriano laid eyes on Princess Bella. Back then, their fledgling romance couldn't survive their controlling families, especially once disaster struck. When they reconnect at a romantic Swiss Alps wedding, a dazzling kiss soon reveals t heir feelings are still there-- and they're begging to be explored! Can they overcome the royal expectations for this duty-bound princess to finally claim their hallily-ever-after?"--back cover.